Process performance optimization and mathematical modelling of a SBR-MBBR treatment at low oxygen concentration. (December 2018) - Ferrentino, Roberta; Ferraro, Alberto; Mattei, Maria Rosaria; Esposito, Giovanni; Andreottola, Gianni
Graphical abstract: Highlights: A SBR-MBBR and A/O-MBBR were investigated for organic carbon and nitrogen removal. COD-TN removal efficiency were 93%–50% for SBR-MBBR and 85%–88% for A/O-MBBR. SBR-MBBR configuration produced less sludge than A/O-MBBR. A mathematical model based on impulsive DEs was developed for the SBR-MBBR process. NRMSE and IoA showed an overall model validity for NH4 + -N and NOx -N prediction. Abstract: In this study, performances of a SBR-MBBR in terms of COD, TN removal efficiency and sludge production were compared to that of an A/O-MBBR. The SBR-MBBR (40% filling ratio) at 24, 18 and 12 h HRT had a COD and TN removal efficiencies of 88 and 75%, 92 and 72%, 90 and 47%. Increasing the filling ratio to 60% with 12 h HRT, the COD and TN removal efficiencies raised to 93% and 66%, respectively. Thus, increasing the filling ratio of the MBBR the TN removal was improved. The A/O-MBBR configuration achieved a COD and TN removal efficiencies, respectively, of 85% and 72%. This configuration obtained the highest sludge yield due to an increase of the sludge production. Nitrification and denitrification activity tests, performed on attached and suspended biomass, revealed a specialization of the microbial community with the suspended biomass responsible for the denitrification process while the attached biomass for the nitrification. Moreover, a mathematical model consisting of a system of impulsive ordinary differential equations was developed to simulate the SBR-MBBR process. The mathematical model was successfully calibrated and validated through the collected experimental data, resulting in a suitable tool for process efficiency prediction and optimization of operational process conditions.